(untitled) (Computer systems and information technologies, 2024)
The task of creating a cyber-physical system for monitoring the environment for allergens is relevant. Therefore, our study is devoted to the development of a method and a cyber-physical system for monitoring the environment for allergens using geolocation data. The developed cyber-physical system for monitoring the environment for allergens not only uses the available information on the activity of pollen sources in a given region, but also measures the concentration of pollen in the air in real time, which helps to monitor the level of pollen in the region where the user is located, and, taking into account the user’s geolocation data, provides him with useful information for route planning to avoid staying in high-risk areas. Collecting and analyzing geolocation data allows you to track changes in the distribution of allergens over time and in space. This can be useful for understanding trends in allergenic reactions and for developing effective allergy management strategies. The cyber-physical system for monitoring the environment for allergens is useful for people with allergies by providing them with accessible and up-to-date information about the environment and the risks of allergic reactions, allowing them to better plan their activities and avoid areas with high levels of plant pollen concentration. Such a cyber-physical system enables an individualized approach to each user, taking into account their unique problems by performing allergen filtering. This allows for effective and personalized allergy management solutions. The proposed cyber-physical system can create a valuable database with allergic reactions and predictions that will be used to improve the methods of diagnosis, treatment and management of allergies. The proposed cyber-physical system can be used for global monitoring of pollen and allergen levels in different parts of the world. This will allow us to identify global trends in the distribution of allergens and develop effective strategies for managing allergies at the global level.